2012
DOI: 10.1039/c2nr11206j
|View full text |Cite
|
Sign up to set email alerts
|

Effects of disorder on the optical properties of CVD grown polycrystalline graphene

Abstract: We explore the effects of crystallite size (L(a)) on the linear and non-linear optical properties of chemical vapor deposition grown polycrystalline graphene. The π-plasmon resonance present at ∼4.75 eV (∼260 nm) in the optical absorption spectrum of graphene follows the empirical relationship λ(π) = 250.5 nm + 89.5 nm(2)/L(a), where λ(π) represents the π-plasmon wavelength. Furthermore, our Z-scan studies reveal that the crystallite size significantly changes the saturation intensity in CVD grown graphene. No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 29 publications
2
41
0
Order By: Relevance
“…The measured saturation intensity is low when compared to the reported values in various spectral ranges, especially at visible range [47][48][49][50][51][52][53][54]. However, it is comparable with the theoretical value [55].…”
Section: Nonlinear Optical Characterizationsupporting
confidence: 56%
See 1 more Smart Citation
“…The measured saturation intensity is low when compared to the reported values in various spectral ranges, especially at visible range [47][48][49][50][51][52][53][54]. However, it is comparable with the theoretical value [55].…”
Section: Nonlinear Optical Characterizationsupporting
confidence: 56%
“…The highest reported values is close to 4 GW cm −2 for single layer graphene [47]. Podila et al have reported that graphene films having less disorder will have the highest saturation intensity owing to its longer recombination time [48]. They reported the lowest value for graphene film having the maximum disorder.…”
Section: Nonlinear Optical Characterizationmentioning
confidence: 94%
“…1 suggesting the role of defects in the NLO properties of doped graphene. Previously NLO studies done on polycrystalline graphene showed that saturation depth increases as a function of the number of graphene layers due to the increase in disorder in the graphene lattice [4]. In the present case too, the highest saturation depths are observed with N3 and N1 which contain maximum number of defects due to the lattice disruption by nongraphitic dopants.…”
Section: Nlo and Raman Measurementsmentioning
confidence: 46%
“…Increase in defects with substitutional doping is further confirmed by the decrease in I S values ( Fig. 2(b)) in the ultrafast regime [6]. Another factor affecting NLO properties in doped nanotubes could be the changes in the metallicity of the nanotubes with B-doping.…”
Section: Nlo and Raman Measurementsmentioning
confidence: 58%